Living Hadis: Implementasi Pembelajaran Al-Qur’an Pada Masyarakat Lansia - Fauziyah, Farichatul; Alfani, Mukhammad (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
This study aims to explore the wisdom and rewards described in the hadith and how it relates to generating enthusiasm for learning the Qur'an among the elderly. It also aims to understand the reaction of the community and the institution TPQ Darul Qur'an to this interest or motivation of the elderly. This research uses a qualitative method, focusing on an objective and realistic description of Qur'anic learning among the elderly. The data collection techniques used by researchers are interviews, observation and documentation. Interviews were conducted with informants who were considered the main sources in this study. The researcher analysed the data through three steps, namely data reduction, data presentation, and conclusion drawing and verification. The results of this study indicate that the rewards or rewards obtained from learning to read the Qur'an are very large. The motivation for the elderly to take part in Quranic learning is their desire to be able to read the Qur'an fluently so that they can be more active in community activities. The community and TPQ Darul Qur'an institutions respond positively to the enthusiasm of these elderly learners and consider it an extraordinary thing and worthy of appreciation.